ASSESSMENT OF POTENTIAL TOURISM RESOURCES IN THE RURAL ENVIRONMENT OF EL KALA (ALGERIA): FROM TYPOLOGY TO THE POSSIBILITY OF IMPLEMENTING POLYSPATIAL TOURISM - Latreche Chafia; Rouag-Saffidine Djamila (International Journal of Innovative Technologies in Social Science, 2024)
Tourism resources are potential for territorial development and tourism diversification. This article presents research on the evaluation of potential tourism resources in the light of the case study of the El Kala region, one of Algeria’s largest National Parks. The aim of this article is to study tourism potential in rural areas, with a view to proposing a typology for the possibility of tourism development, to shed light on this still understudied issue in tourism studies, and to reveal or exploit the potential and local specificities of the El Kala region. This qualitative analysis uses conceptual and institutional approaches to develop a typological model of tourism potential. The theoretical results were then adapted in the field to produce empirical data. The method chosen for data collection is based on an operational approach to compiling a multi-thematic inventory of the region’s tourism potential. These classified potentialities can be used to support, qualify and amplify the creation of polyspatial tourism and new destinations. This approach, built on theoretical approaches and field research, can be used as a decision-making tool to build a sustainable, polyspatial tourism promotional strategy adapted to current challenges, taking into account the region’s strengths and weaknesses.